Understanding preventive behaviors among mid-Western African-American men: a pilot qualitative study of prostate screening - Harvey, Idethia Shevon (2011)
BACKGROUND: African-American men bear a disproportionate burden for disease compared to other ethnic and racial groups. Due to gender differences in socialization and lifestyle practices, men are more likely to adopt attitudes and beliefs that undermine their health and well-being, including beliefs related to masculinity. The purpose of this study was to explore and understand the contextual factors in the attitudes and beliefs of African-American men's view of health in general, and as related to prostate cancer in particular. METHODS: Qualitative data from 15 African-American men were collected from two focus groups and analyzed for common themes using a qualitative descriptive design. RESULTS: Three themes emerged that focused on the beliefs and attitudes regarding general health and prostate cancer screening: (i) traditional beliefs about masculinity; (ii) psychosocial impact from family medical history; and (iii) sexual mores regarding digital rectal exams. CONCLUSIONS: The socialization of African-American men and masculinity ideologies may be significant factors in the focus group member's decisions to seek preventive health behavior changes. Further research is needed to examine the determinants of African-American men's health seeking behavior, in particular on the influence of masculine beliefs.